2020
DOI: 10.3390/ijerph17072505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regular Taekwondo Intervention on Oxidative Stress Biomarkers and Myokines in Overweight and Obese Adolescents

Abstract: Purpose: Regular exercise can alleviate oxidative stress related to obesity and can induce secretion of myokines that are involved in the regulation of metabolic homeostasis. There are no studies examining changes in these variables as a result of Taekwondo training intervention. We aimed to investigate the effect of Taekwondo training on oxidative stress and myokine levels in overweight and obese adolescents. Methods: We randomly assigned 20 overweight and obese adolescents to control (control group; CG, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 46 publications
2
40
0
1
Order By: Relevance
“…The combination of excess production of ROS and inefficient antioxidant capacity generates oxidative stress, which represents one of the main mechanisms underlying the development of obesity [141]. Many studies demonstrated enhancement of the antioxidant barrier (SOD, CAT, GPx, and TAC [141,148,149,151,153]) with a simultaneous decrease of glutathione. The concentration of the products of oxidative damage to proteins (AGE) [151], lipids (MDA) [141,148,151], and DNA (8-OHdG) [142,147,151], as well as total oxidative status, were significantly higher in both saliva and plasma of overweight and obese subjects.…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of excess production of ROS and inefficient antioxidant capacity generates oxidative stress, which represents one of the main mechanisms underlying the development of obesity [141]. Many studies demonstrated enhancement of the antioxidant barrier (SOD, CAT, GPx, and TAC [141,148,149,151,153]) with a simultaneous decrease of glutathione. The concentration of the products of oxidative damage to proteins (AGE) [151], lipids (MDA) [141,148,151], and DNA (8-OHdG) [142,147,151], as well as total oxidative status, were significantly higher in both saliva and plasma of overweight and obese subjects.…”
Section: Obesitymentioning
confidence: 99%
“…The measure of some markers like catalase and TAC could be used to assess the central antioxidant status of overweight and obese [151]. In hypercholesterolemic subjects, the higher level of oxidative stress could be due to a higher concentration of SOD [143,148,151]. Finally, Loffredo et al analyzed the interplay among oxidative stress, NOX2, the catalytic core of NADPH oxidase in children with obesity and/or hypercholesterolemia.…”
Section: Obesitymentioning
confidence: 99%
“…In addition, a 8-week Tai Chi training (a traditional Chinese martial art) increased erythrocyte GPX activity and total plasma antioxidant status in pre-and post-menopausal sedentary women [34]. Additionally, in a study involving 16 weeks of Taekwondo exercise in 20 overweight and obese adolescents, the SOD level was higher and the MDA level significantly lower in the Taekwondo exercise group than in the CG [35]. This reduction in oxidative stress induced as a result of physical activity and exercise as reported in previous studies is similar to our observations, since the exercise intensity of Taekwondo self-defense training in this study was at HRR 40-70%, which is within the range of effective moderate-intensity exercise.…”
Section: Discussionmentioning
confidence: 97%
“…The current study took place under the supervision of a qualified and experienced TKD coach at the Mashhad Taekwondo Home (Razavi Khorasan province, Iran) one month after the end of the provincial TKD season (14). The study began at 11:00 a.m. and lasted for about 1.5 h. The protocol started by jogging and plyometric and stretching exercises for 20 min as a warm-up.…”
Section: Intense Tkd Protocolmentioning
confidence: 99%
“…As a popular combat sport, TKD has been found as a useful exercise regimen for the physical education of students. In this regard, several study groups have suggested that TKD is effective for enhancing physical fitness and growth development and improving body composition in growing participants (14). The TKD athletes, on the other hand, perform intensified technical training and physical fitness in the pre-competition training period.…”
Section: Introductionmentioning
confidence: 99%